Management of the sodium hypochlorite accident: a rare but significant complication of root canal treatment. (25th March 2015) - Hatton, Jonathan; Walsh, Stephen; Wilson, Alan
Abstract : A 66-year-old female patient presented to the accident and emergency department, 3 h following a dental appointment. Significant right-sided facial swelling, bruising and pain were present. The patient had been sent by her general dental practitioner with a covering letter explaining that a hypochlorite accident had occurred during root canal treatment of the upper right first premolar tooth. An iatrogenic perforation was suspected. The patient was admitted under the care of the maxillofacial team and intravenous antibiotics, analgesia and steroids were administered. The patient was prepared for the possibility of requiring surgical intervention under a general anaesthetic. No nerve injury was encountered and the periorbital tissues were spared. A full recovery was made by the patient with no surgical intervention required but significant bruising and swelling were present up to 4 weeks following the incident.